The effects of forward rotation of posture on heavy intensity cycling: Implications of UCI rule 1.3.013 - Caddy, O.; Timmis, M. A.; Gordon, D. (Journal of Science and Cycling, 2015)
UCI rule 1.3.013 limits the forward displacement of the nose of the saddle to 5cm rearward of the centre of the bottom-bracket. This study tests the effects of contravening this rule on 4km laboratory time trials and highlights biomechanical and physiological responses that could be of interest to coaches and bike fitters. Ten competitive male cyclists age 26±2 (mean±SD) yrs, height 180±5 cm, body mass 71±6 kg; VO2max 70.9±8.6 ml/kg·min) completed 4km time trials and heavy intensity bouts. Riding posture was rotated forward where the nose of the saddle was 0, 2, 4, and 6cm to the rear of the bottom bracket (P0, P2, P4 and P6). End time, power, cardiorespiratory responses, lower appendage kinematics and crank torque kinetics were measured. There was no significant effect of position on 4 km time trials completion time or power. During 4 km time trials and heavy intensity bouts, gas exchange variables and lower limb range of motion were unchanged (P>0.05). Trunk lean angle, cardiac output and stroke volume were greater at P6 than other positions (P<0.05). Angular velocity of the hip over top dead centre (350-10°) and the hip peak torque angle were greater at P0 than other positions (P<0.05). Peak and mean torque were unchanged (P>0.05). Results indicate, contravening rule 1.3.013 does not bring about improvements to 4km laboratory TTs. The rearward shift in peak crank torque most likely occurs as a function of altered muscle activation. Haemodynamic variations are possibly related to changes in peripheral resistance at the most forward position. Further work is necessary to allude to probable improvements in aerodynamics.